Three Isothermal Amplification Techniques for Rapid Identification of Cladophialophora carrionii, an Agent of Human Chromoblastomycosis - Deng, Shuwen (American Society for Microbiology, 2014)
In this study, we developed rapid and sensitive assays for the detection of Cladophialophora carrionii, a common agent of human chromoblastomycosis. The isothermal techniques evaluated were rolling-circle amplification (RCA), multiplex ligation-dependent probe amplification (MLPA), and loop-mediated isothermal amplification (LAMP). The probes for RCA and MLPA were designed with target sequences in the rDNA internal transcribed spacer gene (ITS) region, and LAMP primers were designed using the elongation factor 1α gene (EF1); these probes and primers specifically amplified DNA of isolates of the species. The three techniques were sufficiently specific and sensitive for discriminating target DNA of C. carrionii from that of related Cladophialophora species and other agents of chromoblastomycosis. RCA, MLPA, and LAMP are advantageous in their reliability and ease of operation compared to standard PCR and conventional methods.